Urban negotiation, art and the production of public space - O'Kelly, Mick (Risco - Journal of Architecture and Urbanism, 2007)
Urban Negotiations are art strategies that find possibilities for art to engage in the urban environment. Urban Negotiations are collaborative and participatory actions in the production of public and private space. An Artwork for an Imperfect World is a collaborative work with Temple Bar Gallery, Merchants Quay Ireland (NGO) and people suffering homelessness. For a duration the gallery became host, a place of hospitality, were each evening dinner was served from a redesigned Van. The artwork now functions as a mobile needle exchange unit in the streets of Dublin. Nomadic Kitchen is an interstitial art initiative that engages in the process of negotiating the urban environment with the residents of Vila Nova, São Miguel Paulista (São Paulo, Brazil). The structure functions as a locus where residents self govern and develop flexible and creative ways of building a context for living. The structure of Nomadic Kitchen is flexible, fluid, and adaptable to different occasions and contexts. Urban decisions around producing public and social space are made while cooking, eating and meeting in the Nomadic Kitchen. This interstitial structure becomes a place of dialogue while defining the conditions that determine public and private space.